Young individuals' consideration of goal-self alignment and its relations to goal commitment and social concern: age differences and similarities. Issue 6 (2nd November 2019) - Shin, Jongho; Lee, You-kyung; Park, Soowon; Seo, Eunjin
ABSTRACT: We examined middle-school, high-school, and college students in South Korea ( n  = 733) to discern age-related differences in considerations of alignment between life goals and self (i.e., competence, interest, and identity), personal goal commitment, and social concern for others. We also investigated the relations of the alignment considerations to personal goal commitment and social concern for others. Mean-level analyses revealed cross-age differences in alignment considerations, personal goal commitment, and social concern for others. Multiple group analysis, however, showed cross-age similarities; across all ages, all three alignment considerations positively predicted personal goal commitment. Social concern for others, however, was positively predicted only by identity alignment. Results advance our understanding of cross-age similarities and differences in young individuals' life-goal setting and pursuit.